2007
DOI: 10.1161/circulationaha.107.725697
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Short-Term Caloric Restriction Are Mediated by Adiponectin via Activation of AMP-Activated Protein Kinase

Abstract: Background-Overeating and obesity are major health problems in developed countries. Caloric restriction (CR) can counteract the deleterious aspects of obesity-related diseases and prolong lifespan. We have demonstrated that short-term CR improves myocardial ischemic tolerance and increases adiponectin levels. Here, we investigated the specific role of adiponectin in CR-induced cardioprotection. Methods and Results-Adiponectin antisense transgenic (Ad-AS) mice and wild-type (WT) mice were randomly assigned to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 43 publications
5
152
2
Order By: Relevance
“…In the third series of the experiments, hearts were subjected to 25 min of ischemia followed by 120 min of reperfusion with or without IPC. Infarct size was identified by triphenyltetrazolium chloride staining and quantitated as previously described (43,44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the third series of the experiments, hearts were subjected to 25 min of ischemia followed by 120 min of reperfusion with or without IPC. Infarct size was identified by triphenyltetrazolium chloride staining and quantitated as previously described (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…The heart was then quickly excised, and the LV was stored at Ϫ140°C until use. Tissue samples were prepared as previously described (42)(43)(44). For the assessment of the subcellular distribution of Sirt1 protein and cytochrome c, cytosolic and nuclear fractions or cytosolic and mitochondrial fractions were prepared according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiazolidinediones, for example, promote an increased secretion of adiponectin by activating PPAR-γ in adipocytes [61,62]. Caloric restriction has also been shown to increase adiponectin levels and, in turn, confer resistance to myocardial ischemia-reperfusion injury [63]. Recently, a novel nonpharmacological therapeutic intervention, aged garlic extract, was found to increase adiponectin levels in individuals with MetS [64].…”
Section: The Role Of Adiponectin In Metabolic Syndrome and Cardiometamentioning
confidence: 99%
“…Adiponectin is known to promote vascular cell function and survival under stressed condi tions [66,67] . It was recently reported that CR may confer resistance to myocardial ischemia-reperfusion injury by increasing adiponectin levels [68] . Lifelong CR drastically attenuates myocardial oxidative stress during ischemia/reperfusion [23] and post-ischemic inflammatory response [69] .…”
Section: Ischemia and Reperfusionmentioning
confidence: 99%